Comparison of survival outcomes and anatomically specific severe injuries following traffic accidents among occupants of standard and K-car vehicles: A retrospective cohort study at a teaching hospital in Japan. - Yuko Ono; Tasuku Uzawa; Jun Sugiyama; Nozomi Tomita; Takeyasu Kakamu; Tokiya Ishida; Joji Kotani; Kazuaki Shinohara (PLoS ONE)
Road traffic accidents are a global health concern. K-car vehicles, also known as "mini vehicles," are defined as those having an engine displacement <660 cc, vehicle length <3.4 m, width <1.48 m, and height <2.0 m. K-cars have become increasing popular not only in Japan but also in other countries. Compared with standard vehicles, the occupant space of a K-car vehicle is considerably smaller; thus, passengers may be more vulnerable to the external forces generated in a collision, which in turn can lead to deformation of the occupant space and less protection against injuries. However, data are scarce regarding whether K-car vehicles are related to poorer survival outcomes and severe trauma. We conducted a retrospective cohort study involving patients who were injured in four-wheeled vehicle accidents between 2002 and 2023 and admitted to a community teaching hospital in Japan. The vehicle configuration was divided into standard and K-car vehicles. The primary endpoint was in-hospital mortality. Other outcomes included severe trauma, defined as Injury Severity Score (ISS) >15, and anatomically specific severe injury of the head and neck, chest, abdomen, pelvis, and extremities, defined as Abbreviated Injury Scale score ≥3. Of 5331 eligible patients, 2384 (44.7%) were K-car vehicle occupants. In propensity score-matched analysis with 1947 pairs, we observed an increase for in-hospital mortality in the K-car vehicle group (2.6% vs. 4.0%, odds ratio 1.53, 95% confidence interval 1.07-2.19). Compared with standard vehicles, K-car vehicles were associated with a greater risk of severe trauma and serious injuries of the head and neck, chest, abdomen, pelvis, and extremities. These study data should be used to encourage vehicle occupants and automobile manufacturers to consider objective facts regarding the safety of vehicles in a traffic accident.